Band gap reduction of (Mo+N) co-doped TiO2 nanotube arrays with a significant enhancement in visible light photo-conversion: A combination of experimental and theoretical study. (15th June 2021) - Mollavali, Majid; Rohani, Sohrab; Elahifard, Mohammadreza; Behjatmanesh-Ardakani, Reza; Nourany, Mohammad
Abstract: The present research aimed to evaluate the effects of co-doping TiO2 nanotube aligned arrays (TNAs) with molybdenum and nitrogen on photocatalytic activity/performance under visible light irradiation. The surface morphology, electronic and optical properties of the pure and modified TNAs based on experimental characterization and theoretical calculations are reported. Both, pure and doped/modified TNAs were synthesized using a single step/low cost anodization method. Titanium sheets were immersed in ethylene glycol-based electrolytes containing NH4 F and NH4 F + K2 MoO4 to fabricate highly ordered TNAs and Mo-doped TNAs, respectively. Mo–N-doped TNAs were fabricated by a thermal annealing process of Mo-doped samples in nitrogen environment (N2 -gas flow rate of 400 cc/min) for 2hr at 520 °C. Physical/chemical characteristics, structural and photo-electrochemical/electronic properties of the photo-electrodes were observed using several techniques including, field emission scanning electron microscopy (FESEM), Energy Dispersive X-Ray Spectroscopy (EDX), XRD, X-ray photoelectron spectroscopy (XPS), Raman and UV–Vis spectroscopy. We further used a full potential density functional theory (DFT) method to estimate the morphological and electronic structure of the synthesized photo-anodes and also observed a good agreement between theoretical calculations and characterization results. The characterization techniques confirm that Mo and N atoms have been incorporated into the lattice of anodized TNAs and molybdenum atoms partially substituted titanium atoms in the structure of TNAs. UV–Vis DRS spectroscopy experiments and theoretical results reveal that (Mo + N) co-doping creates a positive synergic effect on the band structure of TNAs which can enhance photo-conversion activity, compared to the single Mo/N-doped TNAs samples. In presence of sacrificial agent/electrolyte (aqueous solution of Na2 S/Na2 SO3 ) and visible light irradiation, average photocurrent density of the co-doped TNAs photo-anode is 14 times greater than that of the undoped TNAs. Highlights: Mo + N-co-doped TNAs were synthesized via one step anodization and annealing process. Great agreement between computational DFT results and experimental data. Maximal photocurrent response of 76.66 μA/cm 2 were achieved using co-modified TNAs. An great approach to design new materials with high photocatalytic activity.